THE ACCOUNTING EXCHANGE. - Problem, A C.P.A. (The Accounting Review, 1931)
The student who understands the purpose of a course and who sees how the course will meet his needs has gone far in preparing himself for the study of that course. It is pertinent, therefore, to ask what benefits may be expected from a study of accounting which will justify the necessary expenditure of time. If it be true that the purpose of education is to fit one for living, how does the study of accounting aid in the realization of this aim? Whether one wishes it or not, most students are compelled to spend a large portion of the available time in providing for the necessities of life. The vocational value of bookkeeping and accounting is accepted without question a it is recognized everywhere that efficiency in the use of such knowledge is of direct value to employers. Accounting, however, does more than equip one to hold a mere routine job. Simple record making often leads to more important positions for those who can see beyond boundaries of their first job and who can make use of their experience and opportunities. Accounting provides the background for advancement as it enables one to see how his work fits into the work of other departments. It is not necessary to be a bookkeeper or a public accountant in order to make use of training in accountancy. The subject furnishes one method of learning about the industrial organization of present society.